1996
DOI: 10.1046/j.1365-2567.1996.d01-741.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of CD3‐mediated thymocyte apoptosis by the cross‐linkage of heat‐stable antigen

Abstract: SUMMARYHeat-stable antigen (HSA) is a murine differentiating antigen that is expressed on both CD4 ÿ CD8 ÿ double-negative and CD4 CD8 double-positive thymocytes but not CD4 or CD8 single-positive thymocytes. Effects of anti-HSA monoclonal antibody, R13, on thymocyte apoptosis induced by various stimulations were investigated by a single-cell suspension culture system. Immobilized R13 enhanced the CD3-mediated DNA fragmentation and killing of thymocytes but not the dexamethasoneinduced or phorbol myristate ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
1

Year Published

1999
1999
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
3
1
Order By: Relevance
“…2). Our present findings differ from those of Hitsumoto et al (15) and Punt et al (3), who found that CD24 ligation only enhanced the CD3-mediated death of thymocytes. We assume that this could come from different approaches applied in our system for the detection of apoptotic cells.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…2). Our present findings differ from those of Hitsumoto et al (15) and Punt et al (3), who found that CD24 ligation only enhanced the CD3-mediated death of thymocytes. We assume that this could come from different approaches applied in our system for the detection of apoptotic cells.…”
Section: Discussioncontrasting
confidence: 99%
“…In fact, in human B cell lines, CD24 engagement by specific Abs induces apoptosis, which does not require B cell receptor signaling (16,17). In contrast, CD24 ligation in mouse thymocytes has been reported to enhance CD3-mediated apoptosis, but CD24 engagement alone did not cause thymocyte apoptosis (15).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…Blocking antibodies against CD24 led to non-CD8 + T cell-dependent death of the mice due to possible anaphylaxis when given with vaccine (data not shown). CD24 has also been shown to be involved in apoptosis in B cells and tumor cells as well as T cells indicating that had CD24-blocking antibody not been lethal in those conditions it may have had side effects counterproductive to tumor elimination (4144). …”
Section: Discussionmentioning
confidence: 99%